2021
DOI: 10.1242/jcs.251371
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of YAP in driving TGFβ-mediated endothelial-to-mesenchymal transition

Abstract: Endothelial-to-mesenchymal transition (EndMT) is the biological process through which endothelial cells transdifferentiate into mesenchymal cells. During embryo development, EndMT regulates endocardial cushion formation via TGFβ/BMP signaling. In adults, EndMT is mainly activated during pathological conditions. Hence, it is necessary to characterize molecular regulators cooperating with TGFβ signaling in driving EndMT, to identify potential novel therapeutic targets to treat these pathologies. Here, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 113 publications
(151 reference statements)
0
9
0
Order By: Relevance
“…It has been shown that YAP can prevent GSK3β-mediated Smad3 degradation, thereby promoting Smad3-induced EMT. 366 Furthermore, YAP is physically associated with β-catenin to form a transcriptional complex with TEAD4 in nucleus, leading to the overexpression of EMT-TFs including Slug and Twist in breast cancer. 367 It is worth noting that TEAD4 can regulate EMT and promote metastasis by directly transcribing vimentin without the binding with YAP in colorectal cancer, which is interesting.…”
Section: Hippomentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that YAP can prevent GSK3β-mediated Smad3 degradation, thereby promoting Smad3-induced EMT. 366 Furthermore, YAP is physically associated with β-catenin to form a transcriptional complex with TEAD4 in nucleus, leading to the overexpression of EMT-TFs including Slug and Twist in breast cancer. 367 It is worth noting that TEAD4 can regulate EMT and promote metastasis by directly transcribing vimentin without the binding with YAP in colorectal cancer, which is interesting.…”
Section: Hippomentioning
confidence: 99%
“…Moreover, Hippo signaling can be cross‐linked with other developmental pathways, such as TGFβ and Wnt, to coordinate EMT program. It has been shown that YAP can prevent GSK3β‐mediated Smad3 degradation, thereby promoting Smad3‐induced EMT 366 . Furthermore, YAP is physically associated with β‐catenin to form a transcriptional complex with TEAD4 in nucleus, leading to the overexpression of EMT‐TFs including Slug and Twist in breast cancer 367 .…”
Section: Signalings In Embryonic Development Link To Emtmentioning
confidence: 99%
“…Chromatin binding data for the individual Smad proteins in HE or HSPC/HSCs would be desirable, but will remain a challenge to perform in low cell number samples until good antibodies and new alternatives to conventional ChIP such as Cut&Tag [ 78 ] are standardised. Moreover, Smad proteins only bind to DNA transiently and need transcription factors to stabilise these interactions that additionally increases the difficulty in identifying bona fide binding targets [ 60 , 79 ]. Finally, there is still a need to develop specific compounds to activate or inhibit specific TGFβ receptors and ligands since TGFβ signalling is aberrantly expressed in many diseases [ 80 ].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…A more complex function for SMAD2/3 in EHT can be anticipated from studies on EndoMT. In EndoMT, the Hippo pathway member YAP1 can compete with Smad4 for complex formation with Smad3 during cardiac cushion formation [ 60 ]. The study finds that YAP1/Smad3 complexes have a stronger DNA binding affinity and drive stable transcription of downstream targets [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation